2009
DOI: 10.1063/1.3054184
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic polarizability, Cauchy moments, and the optical absorption spectrum of liquid water: A sequential molecular dynamics/quantum mechanical approach

Abstract: The dynamic polarizability and optical absorption spectrum of liquid water in the 6-15 eV energy range are investigated by a sequential molecular dynamics ͑MD͒/quantum mechanical approach. The MD simulations are based on a polarizable model for liquid water. Calculation of electronic properties relies on time-dependent density functional and equation-of-motion coupled-cluster theories. Results for the dynamic polarizability, Cauchy moments, S͑−2͒, S͑−4͒, S͑−6͒, and dielectric properties of liquid water are rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
19
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 61 publications
3
19
0
Order By: Relevance
“…These effects can potentially be treated by quantum mechanical/molecular mechanical ͑QM/ MM͒ methods [36][37][38] where one or a few water molecules treated at the QM level are surrounded by many MM molecules. Such studies have been reported with the QM part treated by wave function methods 33,[39][40][41][42][43] or by timedependent density functional theory ͑TDDFT͒ methods. 39,[43][44][45] On the other hand, from a supramolecular perspective, the gas-to-liquid blueshift is assigned to excitonic effects, 46,47 and discussed in terms of band structure resulting from energy level splitting of occupied ͑valence band͒ and virtual ͑conduction band͒ orbitals [48][49][50][51][52][53][54] induced by hydrogen bonding and the associated orbital interaction between neighboring molecules.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…These effects can potentially be treated by quantum mechanical/molecular mechanical ͑QM/ MM͒ methods [36][37][38] where one or a few water molecules treated at the QM level are surrounded by many MM molecules. Such studies have been reported with the QM part treated by wave function methods 33,[39][40][41][42][43] or by timedependent density functional theory ͑TDDFT͒ methods. 39,[43][44][45] On the other hand, from a supramolecular perspective, the gas-to-liquid blueshift is assigned to excitonic effects, 46,47 and discussed in terms of band structure resulting from energy level splitting of occupied ͑valence band͒ and virtual ͑conduction band͒ orbitals [48][49][50][51][52][53][54] induced by hydrogen bonding and the associated orbital interaction between neighboring molecules.…”
Section: Introductionmentioning
confidence: 97%
“…Such studies have been reported with the QM part treated by wave function methods 33,[39][40][41][42][43] or by timedependent density functional theory ͑TDDFT͒ methods. 39,[43][44][45] On the other hand, from a supramolecular perspective, the gas-to-liquid blueshift is assigned to excitonic effects, 46,47 and discussed in terms of band structure resulting from energy level splitting of occupied ͑valence band͒ and virtual ͑conduction band͒ orbitals [48][49][50][51][52][53][54] induced by hydrogen bonding and the associated orbital interaction between neighboring molecules. [55][56][57][58] Consequently, excitation energies are no longer strictly properties of individual perturbed molecules, since the excited state is partially delocalized over surrounding water molecules.…”
Section: Introductionmentioning
confidence: 97%
“…Damped linear response properties that have been addressed using damped response theory include one-photon absorption (OPA) spectra and dispersion coefficients, [8][9][10][11][12][13][14][15][16] optical rotation and electronic circular dichroism spectra, [17][18][19][20][21] x-ray absorption and natural circular dichroism spectra, [22][23][24][25][26][27] the dynamic dipole magnetizability, 28 and relativistic linear response functions. 29,30 Damped non-linear molecular properties described by quadratic response theory have been addressed, including Raman scattering, [31][32][33][34][35][36][37][38][39][40][41] the electro-optical Kerr effect and second-harmonic generation, 6 and magnetic circular dichroism.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10][11][12][13][14][15][16] For systems on condensed phase the influence of the medium must also be considered, being the description of solvated systems usually made through simulation methods ͑molecular dynamics or Monte Carlo͒ or continuum models. [17][18][19][20][21][22][23] Methanol has been the subject of a number of recent theoretical and experimental investigations. [24][25][26][27][28][29][30][31] Hyperpolarizabilities of the methanol were reported by Norman et al 32 through the random phase approximation ͑RPA͒ and restricted active space methods using a carefully tested basis set.…”
Section: Introductionmentioning
confidence: 99%